MENINGKATKAN PRODUKTIVITAS MENGAJAR PARA GURU SD AN-NISAA PONDOK AREN DENGAN TEKNOLOGI PENGAJARAN ONLINE INTERAKTIF - Anis Mirza; Sri Wahyuni; Khaerul Ma'mur (JAMAIKA: JURNAL ABDI MASYARAKAT, 2022)
Sectors of life during this pandemic have almost not escaped the effects of the slump so certain tips are needed to keep it running as usual, for example, for education which initially uses conventional face-to-face methods, then is carried out through online meetings. So that online meetings do not bore the object of learning, the teachers who are presenters of lessons need to be stimulated by how interactive online learning is. One of the media is utilizing the hyperlink feature in the PowerPoint application and modifying animation using the Animaker Application so that the goal of increasing teaching productivity during the pandemic is achieved.